The Proline-Rich Family Protein EXTENSIN33 Is Required for Etiolated Arabidopsis thaliana Hypocotyl Growth. (25th April 2020) - Zdanio, Malgorzata; Boron, Agnieszka Karolina; Balcerowicz, Daria; Schoenaers, Sébastjen; Markakis, Marios Nektarios; Mouille, Grégory; Pintelon, Isabel; Suslov, Dmitry; Gonneau, Martine; Höfte, Herman; Vissenberg, Kris
Abstract: Growth of etiolated Arabidopsis hypocotyls is biphasic. During the first phase, cells elongate slowly and synchronously. At 48 h after imbibition, cells at the hypocotyl base accelerate their growth. Subsequently, this rapid elongation propagates through the hypocotyl from base to top. It is largely unclear what regulates the switch from slow to fast elongation. Reverse genetics-based screening for hypocotyl phenotypes identified three independent mutant lines of At1g70990, a short extensin (EXT) family protein that we named EXT33, with shorter etiolated hypocotyls during the slow elongation phase. However, at 72 h after imbibition, these dark-grown mutant hypocotyls start to elongate faster than the wild type (WT). As a result, fully mature 8-day-old dark-grown hypocotyls were significantly longer than WTs. Mutant roots showed no growth phenotype. In line with these results, analysis of native promoter-driven transcriptional fusion lines revealed that, in dark-grown hypocotyls, expression occurred in the epidermis and cortex and that it was strongest in the growing part. Confocal and spinning disk microscopy on C-terminal protein-GFP fusion lines localized the EXT33-protein to the ER and cell wall. Fourier-transform infrared microspectroscopy identified subtle changes in cell wall composition between WT and the mutant, reflecting altered cell wall biomechanics measured by constant load extensometry. Our results indicate that the EXT33 short EXT family protein is required during the first phase of dark-grown hypocotyl elongation and that it regulates the moment and extent of the growth acceleration by modulating cell wall extensibility.